2015
DOI: 10.1039/c5ra06314k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid-leaching on carbon-supported copper phthalocyanine tetrasulfonic acid tetrasodium salt (CuTSPc/C) for oxygen reduction reaction in alkaline electrolyte: active site studies

Abstract: Although non-precious metal catalysts (NPMCs) have been extensively studied as low-cost catalyst alternatives to Pt, in particular for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the nature of the active ORR catalytic sites is still a subject of controversy. In this work, using carbon-supported copper phthalocyanine tetrasulfonic acid tetrasodium salt (CuTSPc/C) nanoparticles as the target catalyst, the effects of the transition metal Cu on the ORR active sites are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…From these results, it can be postulated that Co-NPs have an important catalytic role to play for the ORR reaction . The kinetics of the ORR reaction was also studied using K – L plots (Figure S8); the reaction followed first-order kinetics, and the Co-NC3 catalyst followed the favorable 4e-mechanism (Table S3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…From these results, it can be postulated that Co-NPs have an important catalytic role to play for the ORR reaction . The kinetics of the ORR reaction was also studied using K – L plots (Figure S8); the reaction followed first-order kinetics, and the Co-NC3 catalyst followed the favorable 4e-mechanism (Table S3).…”
Section: Resultsmentioning
confidence: 98%
“…From these results, it can be postulated that have an important catalytic role to play for the ORR reaction. 80 The kinetics of the ORR reaction was also studied using K−L plots (Figure S8); the reaction followed first-order kinetics, and the Co-NC3 catalyst followed the favorable 4e-mechanism (Table S3). As stability is one of the essential parameters for an efficient electrocatalyst, hence, accelerated durability test (ADT) was conducted for the Co-NC3 catalyst at a scan rate of 100 mV/s within the potential range of −1 to 0.2 V versus Ag/AgCl up to 5000 cycles (Figure 5c).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…There are numerous reports on the electrocatalytic properties of carbon materials modified with Co and Fe phthalocyanines and porphyrins and there is a continuously growing research activity in this area [37][38][39]. Whereas the ORR on Cu phthalocyanine (CuPc) and especially on Mn phthalocyanine (MnPc) modified carbon materials is rather poorly investigated compared to aforementioned other transition metal macrocyclic catalysts [21,34,[40][41][42][43][44][45][46][47]. MnPc-based catalysts may reportedly have similar electrochemical behaviour to that of Fe phthalocyanine [41].…”
Section: Introductionmentioning
confidence: 98%
“… 28 Zhang et al were used carbon-supported copper phthalocyanine tetrasulfonic acid tetrasodium salt (CuTSPc/C) nanoparticles as the target catalyst and systematically studied the effects of the transition metal Cu on the ORR active sites. 29 Castro et al reported the synthesis, characterization and catalytic activity of a new Pc coordination polymer and found that the heterogeneous catalytic systems showed a better performance. 30 It can be seen that, compared with the relatively high price of phthalocyanine Co and Fe series catalysts, the catalyst composed of phthalocyanine Cu series and carbon materials has been widely used for its high performance and low cost in oxygen reduction catalysts.…”
Section: Introductionmentioning
confidence: 99%